Respuesta :
To find the difference, subtract.
Here are the steps to solve:
= [tex] \frac{4}{7} - \frac{3}{6} [/tex]
= [tex] \frac{4}{7} + \frac{-3}{6} [/tex]
= [tex] \frac{4}{7} + \frac{-1}{2} [/tex]
= [tex] \frac{8}{14} + \frac{-7}{14} [/tex]
= [tex] \frac{8+-7}{14} [/tex]
[tex]= \frac{1}{14} [/tex]
Here are the steps to solve:
= [tex] \frac{4}{7} - \frac{3}{6} [/tex]
= [tex] \frac{4}{7} + \frac{-3}{6} [/tex]
= [tex] \frac{4}{7} + \frac{-1}{2} [/tex]
= [tex] \frac{8}{14} + \frac{-7}{14} [/tex]
= [tex] \frac{8+-7}{14} [/tex]
[tex]= \frac{1}{14} [/tex]
Turn them both into %
Divide top by bottom and x 100
4/7 (x100) 57.14
3/6 (x100) = 50.00
So 7.14
Divide top by bottom and x 100
4/7 (x100) 57.14
3/6 (x100) = 50.00
So 7.14